2008
DOI: 10.1016/j.jacc.2008.07.062
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Steatosis Is an Independent Predictor of Diastolic Dysfunction in Type 2 Diabetes Mellitus

Abstract: Myocardial triglyceride content is increased in uncomplicated T2DM and is associated with impaired left ventricular diastolic function, independently of age, BMI, heart rate, visceral fat, and diastolic blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

35
407
9
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 493 publications
(457 citation statements)
references
References 32 publications
35
407
9
6
Order By: Relevance
“…A positive age-associated accumulation of TG in the myocardium of rodents, as well as in the myocardium of male human subjects has been shown previously [11,18]. Furthermore, myocardial steatosis is an independent predictor of diastolic function in humans [10,11]. Moreover, pathological conditions, such as obesity and diabetes mellitus, have been shown to be related to mTG content [10,19].…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…A positive age-associated accumulation of TG in the myocardium of rodents, as well as in the myocardium of male human subjects has been shown previously [11,18]. Furthermore, myocardial steatosis is an independent predictor of diastolic function in humans [10,11]. Moreover, pathological conditions, such as obesity and diabetes mellitus, have been shown to be related to mTG content [10,19].…”
mentioning
confidence: 84%
“…For the last decade, it has been known that intracellular triglycerides qualify as biomarkers for chronic diseases of the human organism [9]. Myocardial steatosis (mTG content obtained by 1 H-MRS) was shown to be an independent predictor of diastolic dysfunction in type 2 diabetes mellitus by Rijzewijk et al [10]. Ex vivo as well as in vivo studies revealed that myocardial TG accumulates with increased body mass and, in addition, is relevant to cardiac structure and function [3].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Diabetes is characterised by increased cardiac FA metabolism, with increased mTAG content [156,165,170] and impaired LV function [170]. TAG increases in diabetic hearts on acute fasting accompany diastolic dysfunction [171], though prolonged fasting improves insulin sensitivity, decreases mTAG and improves cardiac function, suggesting a diversion of TAG-derived FA tooxidation [172].…”
mentioning
confidence: 99%